Pendampingan Pengelolaan Bisnis Syariah dalam Meningkatkan Kemandirian Lembaga di Yayasan Islam Al-Lathifah Mulia Cikarang Baratlam Al-Lathifah Mulia Cikarang Barat - Midisen, Kisanda; Badruzzaman, Aceng; Edy, Sarwo; Ahmad, Ali Nur (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2024)
This community service aims to provide information to stakeholders within the scope of the Al-Lathifah Mulia Islamic Foundation about increasing the independence of their institutions by carrying out sharia business management activities in the form of marketing concepts for honey and pure milk. The method used in this community service research is a training and mentoring method provided by providing explanations via Microsoft Power Point. The results of the sharia business management assistance that has been carried out have apparently had a significant positive impact on increasing the independence of institutions at the Al-Lathifah Mulia Islamic Foundation in West Cikarang. One of the positive impacts that can be felt is improving marketing concepts in accordance with sharia business concepts. This can help institutions gain sustainable profits and reduce the risk of unwanted losses. Apart from that, assistance with sharia business management can also help in strengthening the institution's sharia identity. Through the implementation of business practices that comply with sharia principles, institutions can gain the trust of the public who need business services that are in accordance with their religious beliefs.